1990
DOI: 10.1159/000281736
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA Analysis: The Relevance of Ploidy, DNA Heterogeneity and Phases of the Cell Cycle in 329 Patients with Prostatic Carcinoma

Abstract: The ploidy, DNA heterogeneity and the phases of the cell cycle of the tumor were analyzed, by means of single-cell DNA cytophotometry, in 329 patients with locally advanced prostatic carcinoma to find out and establish prognostic factors apart from those already known (stage, grade). Follow-up periods ranged from 1 to 9 years. 253 (76.8%) of the 329 patients had carcinoma stage T3 Nx M₀, and 76 of them (23.1 %) had carcinoma stage T3/T4 N2––4 M<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The majority of T4 as well as grade III tumours were aneuploid, in contrast to grade I tumours which were usually diploid. This is in full agree ment with the previous results [20], including the recent findings by Al-Abadi et al [28] who used single-cell cytophotometry in assessing the DNA content and cell phase of cancer cells. Distribution of DNA indexes was similar to that reported by Haugen et al [29] who also found a significant proportion of tumours to have a nearly tetraploid or tetraploid DNA index.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of T4 as well as grade III tumours were aneuploid, in contrast to grade I tumours which were usually diploid. This is in full agree ment with the previous results [20], including the recent findings by Al-Abadi et al [28] who used single-cell cytophotometry in assessing the DNA content and cell phase of cancer cells. Distribution of DNA indexes was similar to that reported by Haugen et al [29] who also found a significant proportion of tumours to have a nearly tetraploid or tetraploid DNA index.…”
Section: Discussionsupporting
confidence: 92%
“…Most DNA ploidy studies in prostate carcinoma have been performed using flow cytometry [4,20,24-28, 30-32,391. Smaller numbers of researchers have employed image analysis [19,29,33,40,41], and limited numbers of studies have addressed the comparison and reliability of different techniques 142,431.…”
Section: Introductionmentioning
confidence: 99%
“…• 32 revealed an inadequate study design: 10 comprised < 50 patients [54][55][56][57][58][59][60][61][62][63], 6 had a mixture of different types of therapy [64][65][66][67][68][69], 5 missed sufficient therapeutic information [70][71][72][73][74], 3 missed sufficient follow-up information [75][76][77], 4 applied an inadequate gold standard (digital rectal examination, cancer volume) [78][79][80][81], 2 selected prognostically extreme groups of patients [82,83], 1 comprised mixed tumor-stages [84], 1 presented no details on recurrence [85].…”
Section: Excluded Papersmentioning
confidence: 99%